New insights into reproductive physiology in Antarctic fish: a trial in Lepidonotothen nudifrons - Novillo, Manuel; Elisio, Mariano; Moreira, María Eugenia; Macchi, Gustavo Javier; Barrera Oro, Esteban (Polar Biology)
The spatio-temporal delimitation of fish reproduction is essential for the appropriate management and conservation strategies in populations. Assessing this feature in Antarctic Ichthyology is particularly difficult because harsh environmental conditions limit sample collection. This study shows how physiology can contribute compelling evidence to understand reproduction in Antarctic fish using the notothenioid Lepidonotothen nudifrons as a model species. Sampling included 121 specimens caught at Potter Cove (PC), South Shetland Islands (SSI), from November to late March of 2016–2018. Gonadal macroscopic and histologic features are reported. Oocyte growth and change in testosterone and estradiol plasma levels throughout the ovarian growth of L. nudifrons adult females is provided. In March, females (n = 17) attained gonado-somatic index of 13–20% (16.73 ± 4.20), total fecundity of 2196–4652 oocytes/female, the leading clutch oocytes measured 1.7–2.1 mm, and males (n = 5) showed spermatozoids in their testicles. The leading clutch growth was significantly associated with photoperiod, with no diameter variation until the summer solstice, when it began to grow linearly with an estimated rate of 0.01 mm/day. Testosterone and estradiol increased together with the oocyte growing throughout the analysed months, with a higher rate of increase during March. The reproductive effort data, and especially the significant plasma level increase in both sex steroids observed in March, suggest that (1) females were at a late vitellogenesis stage, just prior to the oocyte final maturation, and thus L. nudifrons spawning period might begin in March at SSI; (2) PC is likely a spawning site for L. nudifrons, which indicates that nearshore areas are spawning grounds for some notothenioids. Fil: Novillo, Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Elisio, Mariano. Consejo ...